Air pollution-regulated E-cadherin mediates contact inhibition of proliferation via the hippo signaling pathways in emphysema - Chang, Jer-Hwa; Lee, Yueh-Lun; Laiman, Vincent; Han, Chia-Li; Jheng, Yu-Teng; Lee, Kang-Yun; Yeh, Chi-Tai; Kuo, Han-Pin; Chung, Kian Fan; Heriyanto, Didik Setyo; Hsiao, Ta-Chih; Wu, Sheng-Ming; et al. (ScienceDirect, 2022)
Air pollution has been linked to emphysema in chronic obstruction pulmonary disease (COPD). However, the underlying mechanisms in the development of emphysema due to air pollution remain unclear. The objective of this study was to investigate the role of components of the Hippo signaling pathway for E-cadherin-mediated contact inhibition of proliferation in the lungs after air pollution exposure. E-Cadherin-mediated contact inhibition of proliferation via the Hippo signaling pathway was investigated in Sprague-Dawley (SD) rats whole-body exposed to air pollution, and in alveolar epithelial A549 cells exposed to diesel exhaust particles (DEPs), E-cadherin-knockdown, and high-mobility group box 1 (HMGB1) treatment. Underlying epithelial differentiation, apoptosis, and senescence were also examined, and the interaction network among these proteins was examined. COPD lung sections were used to confirm the observations in rats. Expressions of HMGB1 and E-cadherin were negatively regulated in the lungs and A549 cells by air pollution, and this was confirmed by knockdown of E-cadherin and by treating A549 cells with HMGB1. Depletion of phosphorylated (p)-Yap occurred after exposure to air pollution and E-cadherin-knockdown, which resulted in decreases of SPC and T1α. Exposure to air pollution and E-cadherin-knockdown respectively downregulated p-Sirt1 and increased p53 levels in the lungs and in A549 cells. Moreover, the protein interaction network suggested that E-cadherin is a key activator in regulating Sirt1 and p53, as well as alveolar epithelial cell differentiation by SPC and T1α. Consistently, downregulation of E-cadherin, p-Yap, SPC, and T1α was observed in COPD alveolar regions with particulate matter (PM) deposition. In conclusion, our results indicated that E-cadherin-mediated cell-cell contact directly regulates the Hippo signaling pathway to control differentiation, cell proliferation, and senescence due to air pollution. Exposure to air pollution may initiate emphysema in COPD patients.